2012
DOI: 10.1124/dmd.112.045054
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Absolute Protein Quantification of Carboxylesterases 1 and 2 in Human Liver Tissue Fractions using Liquid Chromatography-Tandem Mass Spectrometry

Abstract: ABSTRACT:The aims of this study were to develop a robust method for simultaneous quantification of carboxylesterases (CESs) 1 and 2 and to quantify those absolute protein levels in human liver tissue fractions. Unique peptide fragments of CES1 and CES2 in tryptically digested human liver microsomes (HLMs) and cytosol (HLC) were simultaneously quantified by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) using corresponding stable isotope-labeled peptides as internal standards. Bovine ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 26 publications
6
40
0
Order By: Relevance
“…For example, CES1 abundance in the liver is ;20-to 30-fold higher than the most abundant adult cytochrome P450 enzyme, CYP3A4 (Achour et al, 2014). Interestingly, although the absolute abundance values of CES1 and CES2 presented in this study are consistent with those reported by other LC-MS/MS proteomics studies (Sato et al, 2012;Wang et al, 2016), the values reported by Hines et al (2016) are significantly lower, which might be due to the methodological differences (i.e., LC-MS/MS proteomics versus immunoblotting).…”
Section: Discussionsupporting
confidence: 90%
“…For example, CES1 abundance in the liver is ;20-to 30-fold higher than the most abundant adult cytochrome P450 enzyme, CYP3A4 (Achour et al, 2014). Interestingly, although the absolute abundance values of CES1 and CES2 presented in this study are consistent with those reported by other LC-MS/MS proteomics studies (Sato et al, 2012;Wang et al, 2016), the values reported by Hines et al (2016) are significantly lower, which might be due to the methodological differences (i.e., LC-MS/MS proteomics versus immunoblotting).…”
Section: Discussionsupporting
confidence: 90%
“…However, human CES1 is also expressed in the lung, heart, and kidney, though to a lesser extent (Satoh et al, 2002). This dominant CES1 expression relative to CES2 in the liver was also confirmed by proteomic data, with an average protein expression level of 402 and 30 pmol/mg protein reported in human liver microsomes for CES1 and CES2, respectively (Sato et al, 2012). In addition to the small intestine, human CES2 mRNA data have also been reported for the kidney and to a minor extent for the colon and heart (Satoh et al, 2002;Quinney et al, 2005).…”
Section: Introductionsupporting
confidence: 58%
“…To select proteotypic peptides that could be digested efficiently, we preliminarily analyzed tryptic digests of rhUGTs using enhanced mass spectrometry scanning, and identified peptide fragments by ProteinPilot (AB SCIEX) according to a published method (data not shown) (Sato et al, 2012a). Proteoptypic peptides identified with the highest confidence values here or reported to yield highly reproducible quantities by others were selected as analytes (Supplemental Table 1) (Fallon et al, 2008;Harbourt et al, 2012;Sato et al, 2012b;Fallon et al, 2013b).…”
Section: Lc-multiple Reaction Monitoringmentioning
confidence: 99%